The Esophageal Cancer and the PI3K/AKT/mTOR Signaling Regulatory microRNAs: a Novel Marker for Prognosis, and a Possible Target for Immunotherapy - Javadinia, Seyed A.; Shahidsales, Soodabeh; Fanipakdel, Azar; Mostafapour, Asma; Joudi-Mashhad, Mona; Ferns, Gordon A.; Avan, Amir (Current Pharmaceutical Design, 2018)
The Phosphatidylinositol 3-kinase/AKT/Mammalian Target of Rapamycin (PI3K/AKT/mTOR) pathway has a critical regulatory role in cell biology including translation, transcription, and autophagy. Dysregulation of this pathway is involved in the pathogenesis, development, and prognosis of esophageal cancer that has been assessed in the recent years and its potential as a target in therapy. This report summarizes the current knowledge about PI3K/AKT/mTOR pathway and its cross-talk with a focus on the value of targeting this pathway as a potential therapeutic target in the treatment of esophageal cancer.
Keywords: transcription